Lithofacies analysis and reservoir potential of the Belait formation, Labuan Island, Malaysia - Hafzan Eva Mansor (2012)
The Neogene sedimentary rocks of the Labuan Island consist of two lithostratigraphic units – the Setap Shale Formation (Middle Miocene) and the Belait Formation (Late Miocene). The sandstones are very fine to conglomeratic, moderately well-sorted to well-sorted, texturally and mineralogically mature quartz arenites, with subordinate subliharenites. The field characteristic of the clastic sequence of the Neogene sediments were studied using lithofacies analysis and interpreted to have deposited within the prograding shoreface sequence consists of upward coarsening unit. Combining information from trace fossils and sedimentary structures allow the subdivision of the sequence into deposits of the foreshore (Lithofacies A), upper shoreface (Lithofacies B), lower shoreface (Lithofacies C), and distal lower shoreface to inner shelf (Lithofacies D). The sedimentary structures found can be interpreted as a product of a combination of both bed load sediment transport and sediment falling out of suspension. The Neogene reservoir interval comprises two lithofacies association; storm and wave-dominated middle shoreface to inner-shelf (Lithofacies Association 1), and wave-dominated upper shoreface and foreshore (Lithofacies Association 2). Very good quality reservoir rocks were represented by Lithofacies B (average RQI is 1.322). The poorest quality of reservoir rocks is Lithofacies D (average RQI is 0.108). Low reservoir permeability (generally less than 1mD) and porosity (less than 20%) are interpreted to be the result of early compaction, cementation, and diagenesis. The Belait sandstone diagenetic processes include clay infiltration, compaction and cementation (quartz overgrowth, calcite, kaolinite, trace amount of K-feldspar overgrowth, and illite). Quartz is the dominant pore occluding cement and generally occurred as small euhedral crystal, locally as large pyramidal crystals in the primary pores. Pressure solution derived from grain contact is the main contributor of quartz overgrowth. Calcite occurs as pore filling. Kaolinite locally developed similarly like ‘book sheets’ and authigenic illite exhibits fibrous morphology filling pores. These clays enhance ineffective microporosity. Porosity and permeability data exhibit good inverse correlation with cement. However, some data points indicate multiple controls on permeability. Reservoir quality thus controlled by other factors such as pore occluding cement, textural parameters (grain size, pore size, and sorting), depositional environment, and diagenesis.